Development of Land Conflict Settlement Model Based on Indigenous Knowledge of the Local Communities in Indonesia - Sunarno, Sunarno (Indonesian Comparative Law Review, 2019)
Land conflict has become a classic issue in Indonesia and an effective dispute settlement seems to be urgent. The study aims at evaluating the possibility to incorporate the indigenous knowledge of the local communities in land dispute settlement system. This socio-legal research employs both qualitative and quantitative approach.It is found that the current legal and institutional systems are not in accordance with the legal consciousness of the Indonesian society. The purposes of agrarian policy have been controlled by the domination of the state over the people’s rights. The policies were made to safeguard the interests of elite and its supporters and at the same times ignore the society interests. As the old model of land dispute settlement, the Dutch procedural law (HIR) served the colonial interest. In fact, there are statutory provisions in the sector of natural resources and land that regulate land dispute settlement that accommodate the local wisdom. In addition, article 18 of the 1945 Constitution and Article 5 of the Basic Agrarian Law explicitly recognize the capacity of the indigenous people in settling land dispute. However it needs further elaboration and institutionalization of their values. The development of a legal system model based on local community wisdom is a must which it means a legal system that is incorporated from the value of the original legal system of the Indonesian nation. The Indonesian customary legal system rests on the concept of regional values that exist throughout Indonesia regions.